Flow of granular matter in a silo with multiple exit orifices: jamming to mixing - Kamath, Sandesh; Kunte, Amit; Doshi, Pankaj; Orpe, Ashish V. (Physical Review E, 2014)
We investigate the mixing characteristics of dry granular material while draining down a silo with multiple exit orifices. The mixing in the silo, which otherwise consists of noninteracting stagnant and flowing regions, is observed to improve significantly when the flow through specific orifices is stopped intermittently. This momentary stoppage of flow through the orifice is either controlled manually or is chosen by the system itself when the orifice width is small enough to cause spontaneous jamming and unjamming. We observe that the overall mixing behavior shows a systematic dependence on the frequency of closing and opening of specific orifices. In particular, the silo configuration employing random jamming and unjamming of any of the orifices shows early evidence of chaotic mixing. When operated in a multipass mode, the system exhibits a practical and efficient way of mixing particles.

Fingering instability in the flow of a power-law fluid on a rotating disc - Arora, Akash; Doshi, Pankaj (Physics of Fluids, 2016)
A computational study of the flow of a non-Newtonian power law fluid on a spinning disc is considered here. The main goal of this work is to examine the effect of non-Newtonian nature of the fluid on the flow development and associated contact line instability. The governing mass and momentum balance equations are simplified using the lubrication theory. The resulting model equation is a fourth order non-linear PDE which describes the spatial and temporal evolutions of film thickness. The movement of the contact line is modeled using a constant angle slip model. To solve this moving boundary problem, a numerical method is developed using a Galerkin/finite element method based approach. The numerical results show that the spreading rate of the fluid strongly depends on power law exponent n. It increases with the increase in the shear thinning character of the fluid (n < 1) and decreases with the increase in shear thickening nature of the fluid (n > 1). It is also observed that the capillary ridge becomes sharper with the value of n. In order to examine the stability of these ridges, a linear stability theory is also developed for these power law fluids. The dispersion relationship depicting the growth rate for a given wave number has been reported and compared for different power-law fluids. It is found that the growth rate of the instability decreases as the fluid becomes more shear thinning in nature, whereas it increases for more shear thickening fluids. (C) 2016 AIP Publishing LLC.

Fingering instability of a suspension film spreading on a spinning disk - Kulkarni, Mayuresh; Sahoo, Subhadarshinee; Doshi, Pankaj; Orpe, Ashish V. (Physics of Fluids, 2016)
The spreading of a thin film of suspension on a spinning disk and the accompanying contact line instability is studied through flow visualization experiments. The critical radius for the onset of instability shows an increase with increase in the particle fraction (phi(p)) before decreasing slightly at the highest value of phi(p) studied, while the instability wavelength (lambda) exhibits a non-monotonic dependence. The value of lambda is close to that for a partially wetting liquid at lower phi(p), it decreases with increasing phi(p) to a minimum before increasing again at largest phi(p). The non-monotonic trends observed for lambda are discussed in light of the linear stability analysis of thin film equations derived for suspensions by Cook et al. [''Linear stability of particle-laden thin films,'' Eur. Phys. J.: Spec. Top. 166, 77 (2009)] and Balmforth et al. [''Surface tension driven fingering of a viscoplastic film,'' J. Non Newtonian Fluid Mech. 142, 143 (2007)]. Published by AIP Publishing.

Friction-mediated flow and jamming in a two-dimensional silo with two exit orifices - Orpe, Ashish V.; Doshi, Pankaj (Physical Review E, 2019)
We show that the interparticle friction coefficient significantly influences the flow and jamming behavior of granular materials exiting through the orifice of a two-dimensional silo in the presence of another orifice located in its vicinity. The fluctuations emanating from a continuous flow through a larger orifice results in an intermittent flow through the smaller orifice consisting of sequential jamming and flowing events. The mean time duration of jammed and flow events, respectively, increase and decrease monotonically with increasing interparticle friction coefficient. The frequency of unjamming instances (n(u)), however, shows a nonmonotonic behavior comprising an increase followed by a decrease with increasing friction coefficient. The decrease on either side of the maximum, then, represents a system moving progressively towards a permanently jammed or a permanently flowing state. The overall behavior shows a systematic dependence on the interorifice distance, which determines the strength of the fluctuations reaching the smaller orifice leading to unjamming instances. The probability distributions of jamming and flowing times are nearly similar for different combinations of friction coefficients and interorifice distances studied and, respectively, exhibit exponential and power-law tails.

Flow of lubricated granular material on an inclined plane - Ghodake, Ravindra S.; Doshi, Pankaj; Orpe, V. Ashish (Powder Technology, 2022)
We have studied the gravity driven flow of spherical shaped, millimetric sized granular material coated with aspherical, micron-sized, near frictionless lubricant particles. Experiments were performed on an inclined plane using two different sized particles for varying concentrations of the lubricant. The particle volumetric flow rate exhibits a non-monotonic behavior with increasing lubricant concentration. It shows an increase at lower lubricant concentration followed by a decrease at higher lubricant concentration. The lubricant particles adhere to the granular particle surface thereby reducing the inter-particle friction. However, presence of lubricant particles at higher concentration damps out inter-particle collision thereby reducing the inter-particle momentum transfer. Non-monotonicity in the observed behavior is then conjectured to arise due to competing effects of inter-particle friction and inter-particle collision. The present work and the overall observed behavior therein provides a simple experimental system to characterize the effects of added lubricant material in pharmaceutical and other relevant industrial applications.
Keywords: Friction; granular; Inclined plane; Lubrication; Powder

Flow and clogging behavior of a mixture of particles in a silo - Bhure, Sukhada C.; Doshi, Pankaj; Orpe, Ashish V. (Physics of Fluids, 2024)
We investigated the clogging behavior observed during the flow of aspherical particles from a silo in the presence of spherical particles of different sizes and proportions using flow visualization experiments and discrete element method simulations. The size of the avalanche, essentially the tendency of clogging, exhibits non-monotonic dependence on the spherical particle volume fraction. For small enough content of spherical particles, the clogging tendency intensifies, whereas it reduces rapidly for high enough spherical particle fractions, with a minimum in between. The non-monotonic behavior is observed to persist over for different spherical particle sizes. The overall behavior is shown to arise due to competing effects between the localized total particle fraction influencing avalanche strength and mean size of the particles exiting the silo, influencing the probability of arch formation.